Parents' Socioeconomic Status and Lifestyle Influence on Student Consumption - Adriani, Evi (International Journal of Multidisciplinary Sciences and Arts, 2024)
The aim of this research is to find out whether parents' socio-economic status and lifestyle have a partial or simultaneous effect on consumption among students at the Faculty of Economics, Batanghari University, Jambi. This research is field research (Field Research) using descriptive analysis methods with a quantitative approach. Data collection techniques in this research used questionnaires and documentation. The sample was 94 students from the Faculty of Economics, Batanghari University, Jambi, taken using simple random sampling. The data analysis method uses the Multiple Linear Regression Analysis method, the coefficient of determination test (R2), and hypothesis testing, namely the F Test and t Test. The results of the research show that simultaneously or partially, parents' socio-economic status and lifestyle have a significant and positive effect on the consumption of students at the Faculty of Economics, Batanghari University. The R Square value is 0.176, which means that the variables of parents' socio-economic status and lifestyle can explain 17.6% of student consumption, while the remaining 82.4% is explained by other variables. This research concluded that partially Lifestyle (X2) has a significant and positive effect on the consumption of economics faculty students at Batanghari University, Jambi (Y), meaning that if lifestyle increases, consumption of economics faculty students at Batanghari Jambi University will also increase.